Cantharidin inhibits competitively heme‐Fe(III) binding to the FA1 site of human serum albumin. Issue 11 (13th June 2017) - Polticelli, Fabio; Leboffe, Loris; Tortosa, Valentina; Trezza, Viviana; Fanali, Gabriella; Fasano, Mauro; Ascenzi, Paolo
Abstract: Cantharidin, a monoterpene isolated from the insect blister beetle, has long been used as a medicinal agent in the traditional Chinese medicine. Cantharidin inhibits a subgroup of serine/threonine phosphatases, thus inducing cell growth inhibition and cytotoxicity. Cantharidin has anticancer activity in vitro, since it is able of inducing p53‐dependent apoptosis and double‐strand breakage of DNA in cancer cells. Although the toxicity of cantharidin to the gastrointestinal and urinary tracts prevents its medical use, it is a promising lead compound for chemical modification to develop new anticancer therapeutics. In fact, cantharidin does not cause myelosuppression and displays anticancer activity against cells with a multidrug resistance phenotype. Here, the competitive inhibitory effect of cantharidin on heme‐Fe(III) binding to the fatty acid site 1 (FA1) of human serum albumin (HSA) is reported. Docking and molecular dynamics simulations support functional data indicating the preferential binding of cantharidin to the FA1 site of HSA. Present results may be relevant in vivo as HSA could transport cantharidin, which in turn could affect heme‐Fe(III) scavenging by HSA. Abstract : Cantharidin, a monoterpene isolated from the insect blister beetle, has long been used as a medicinal agent in the traditional Chinese medicine, inducing cell growth inhibition, cytotoxicity, and anticancer activity in vitro . Cantharidin inhibits competitively heme‐Fe(III) binding to the FA1 site of human serum albumin. This suggests that cantharidin could affect heme‐Fe(III) transport by human serum albumin.